Evaluation of a new rebound tonometer for self-measurement of intraocular pressure - Dabasia, Priya L; Lawrenson, John G; Murdoch, Ian E (British journal of ophthalmology, 2016)
Background/aimsTo compare the accuracy of self-obtained, partner-obtained and trainer-obtained measurements using the handheld Icare Home rebound tonometer with Goldmann applanation tonometry (GAT), and to evaluate the acceptability to subjects of Icare Home measurement.Methods76 subjects were trained to use Icare Home for self-measurement using a standardised protocol. A prespecified checklist was used to assess the ability of a subject to perform self-tonometry. Accuracy of Icare Home self-measurement was compared with GAT using one eye per subject, randomly selected. Bland-Altman difference analysis was used to compare Icare Home and GAT intraocular pressure (IOP) estimates. Acceptability of self-tonometry was evaluated using a questionnaire.Results56 subjects (74%, 95% CI 64 to 84) were able to correctly perform self-tonometry. Mean bias (95% limits of agreement) was 0.3 mm Hg (−4.6 to 5.2), 1.1 mm Hg (−3.2 to 5.3) and 1.2 mm Hg (−3.9 to 6.3) for self-assessment, partner-assessment and trainer-assessment, respectively, suggesting underestimation of IOP by Icare Home tonometry. Differences between GAT and Icare Home IOP were greater for central corneal thickness below 500 µm and above 600 µm than data points within this range. Acceptability questionnaire responses showed high agreement that the self-pressure device was easy to use (84%), the reading was quick to obtain (88%) and the measurement was comfortable (95%).ConclusionsIcare Home tonometry can be used for self-measurement by a majority of trained subjects. IOP measurements obtained using Icare Home tonometry by self-assessment and third party-assessment showed slight underestimation compared with GAT.